KINERJA NONLINIER RANGKA BAJA TER–BREIS KONSENTRIK KHUSUS PADA RENTANG KETINGGIAN 48-80 METER - Prabowo, Andy; Silvester Boenyamin, Michael; Wijaya, Hendy (JURNAL TEKNIK SIPIL CENDEKIA (JTSC), 2025)
This study analyzes the nonlinear performance of Special Concentrically Braced Steel Frames (SCBF) in high-rise buildings exceeding the height limits stipulated in SNI 1726 (48 meters). Three case studies were selected, which are steel buildings with 48 (for benchmarking), 64, and 80-meter heights. Motivated by the urban demand for space efficiency and the crucial need for seismic resistance in steel structures, this study aims to evaluate the ductility and plastic hinge behavior of SCBF in multi-storey steel buildings. The primary objectives are to analyze SCBF structural performance, compare ductility parameters ) based on design and first yield results, and determine forces and deformations in braces during Design Basis Earthquake (DBE) and Maximum Considered Earthquake (MCE) events. The methodology involves nonlinear pushover analysis using MIDAS GEN 2024 software, including plastic hinge and fiber element modeling. The results indicate that SCBF performance in 48 and 64 m building heights experienced plastic hinge failure in the braces during MCE, yet met DBE limitations. Only the 20-story building satisfied MCE limits. Comparisons of  and  values show consistency with the design plan but are lower at first yield compared to SNI 1726.